Analysis of the Role of Teacher’s Parenting Styles on Student Learning Motivation at State Vocational Schools in Surakarta - Laila, Fika Adin; Maryono, Dwi; Wardani, Dwi Esti (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2024)
The motivation of students to learn is greatly influenced by their teachers. Teachers are significant figures in the classroom who can uplift and mentor students. The parenting and teaching styles of educators can foster an atmosphere that encourages students to become motivated learners. A spirit of learning can be fostered by teachers who can offer constructive criticism, offer challenges that are appropriate for their student's abilities, and pay attention to each student's personal growth. The purpose of this research is to ascertain how teacher parenting influences students' motivation to learn. Teachers and students are the study's subjects, and a qualitative descriptive method is being used. Three methods were employed to acquire the data: observation, interviews, and documentation. Data analysis used descriptive qualitative data analysis. The results of the study show that the dominant teacher parenting in motivating student learning is democratic parenting. This parenting style emphasizes open communication, giving freedom of expression, and instilling positive values in students. Democratic parenting can increase student learning motivation because it can make students feel valued, recognized, and in control of themselves. In addition, democratic parenting can also shape students' positive characteristics, such as discipline, independence, and communication. These positive characteristics can support students in learning and achieving maximum achievement.